Aplicación móvil enfocada como estrategia pedagógica en los diagnósticos, manejo y tratamientos endodónticos para los estudiantes UAN - Rojas Sarmiento, Ana Maryeli; Sosa Aguirre, Alexandra; Burgos Mora, Cristian Andres (Universidad Antonio Nariño, 2022)
A didactic interface was developed, which will allow the student to easily, quickly and didactically obtain all the information on the different diagnoses, management and endodontic treatments; thus guaranteeing the success of students when diagnosing any endodontic pathology.